2008
DOI: 10.1111/j.1464-410x.2008.07570.x
|View full text |Cite
|
Sign up to set email alerts
|

Robotic salvage retropubic prostatectomy after radiation/brachytherapy: initial results

Abstract: OBJECTIVE To report on the initial four patients who had robotic salvage retropubic prostatectomy (SRP) for biochemical recurrence after radiation therapy, and to review the surgical outcome of robotic cystoprostatectomy for bladder cancer in two patients who previously had prostate cancer. PATIENTS AND METHODS Since February 2006, four patients had SRP for biochemical failure after radiation and/or brachytherapy. Transrectal biopsy of the prostate confirmed locally recurrent disease and a metastatic evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 17 publications
0
60
0
2
Order By: Relevance
“…Kaouk et al [23] reported on the initial 4 patients who had SRARP for BCR after radiotherapy for PCa. Three patients were continent within a month while 1 continued to use 2-3 pads/day at 3-week follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaouk et al [23] reported on the initial 4 patients who had SRARP for BCR after radiotherapy for PCa. Three patients were continent within a month while 1 continued to use 2-3 pads/day at 3-week follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…As more experience is being gained with robotic techniques, surgeons are expanding its application to more technically challenging procedures. In fact, recent case reports have described the feasibility of salvage RARP (SRARP), suggesting the robotic approach to be technically feasible, offering equivalent oncological outcomes and less convalescence than the open approach [20,21,22,23,24,25]. The objective of this study was to evaluate the surgical, oncological and functional outcomes in patients undergoing SRARP for the treatment of radiation-resistant PCa and to contribute our experience to the small amount of contemporary literature that exits on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Además, existe un mayor riesgo de lesión rectal durante la PR en el territorio irradiado, que probablemente condenará al paciente a una colostomía definitiva. Incluso mediante abordajes laparoscópicos o robóticos, y aun siendo técnicamente factibles, se observa mayor morbilidad 12 . El problema se evidencia sobre todo en el perfil de paciente sano y con larga expectativa de vida, donde además de que la PR de rescate aumentará severamente la morbilidad, el resto de alternativas locales de rescate existentes (crioterapia, HIFU [High Intensity Focused Ultrasround]) no tienen ni un seguimiento ni una evidencia científica suficiente para ser recomendadas, y están expuestas a importante morbilidad cuando se aplican como rescate post-RT.…”
Section: Resultados Funcionalesunclassified
“…Treatment results could be improved if salvage therapy is considered very early in the disease process. SRARP is technically possible and with limited perioperative morbidity [18]. This curative therapy may be underutilized in biochemical recurrence [19].…”
Section: Resultsmentioning
confidence: 99%